The ins and outs of Central European unemployment. Issue 1 (2nd January 2022) - Flek, Vladislav; Hála, Martin; Mysíková, Martina
ABSTRACT: We examine the role of unemployment inflows and outflows in contributing to unemployment cyclicality in Czechia and Poland, using data from the European Union Statistics on Income and Living Conditions, and a three-state model of unemployment variance decomposition. We find that the labour market fluidity is higher in Poland than in Czechia, with Polish workers moving in and out of unemployment more frequently than their Czech counterparts. For both countries, the upward unemployment dynamics was during 2008–2011 driven by counter-cyclical increases in the job-separation rate, rather than by pro-cyclical declines in the job-finding rate. The inflow-outflow split was nonetheless more balanced in Czechia. The two economies further diverged across 2015–2018: Czech unemployment declined prevailingly due to diminishing job separations, while in Poland it was mostly due to improving job-finding prospects. This signals a deeper insider-outsider fragmentation of the Czech labour market, even during the period of economic expansion.